Hierarki Kejelasan Makna dalam Uṣūl al-Fiqh: Reinterpretasi Ẓāhir hingga Muḥkam dalam Penetapan Hukum Islam - Muhammad Didit Dermawan Rola; Amrudin Amrudin; Fatmawati Fatmawati; Zainal Abidin (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2026)
This article discusses the hierarchy of semantic clarity in Islamic legal theory (uṣūl al-fiqh), which consists of ẓāhir, naṣṣ, mufassar and muḥkam, and its implications for Islamic legal reasoning (istinbāṭ al-ḥukm). The aim of this study is to explain the concept of ẓāhir al-dalālah as the initial level of meaning that still allows for interpretation (ta’wīl), as well as the relationship between the levels of clarity in determining the strength of legal evidence. This research uses a library-based approach by examining classical and contemporary works in uṣūl al-fiqh. The findings show that each level has different characteristics and legal authority. Ẓāhir refers to a meaning that is directly understood but still open to interpretation (ta’wīl). Naṣṣ is stronger because it reflects the primary intent of the text, while mufassar provides more detailed and explicit clarification. Muḥkam represents the highest level of clarity, as it is definitive and does not allow interpretation (ta’wīl) or abrogation (naskh). In conclusion, the hierarchy of semantic clarity serves as an essential methodological framework in Islamic legal reasoning, particularly in resolving textual differences. It ensures consistency, precision, and objectivity in interpreting the Qur’an and Sunnah.